2008
DOI: 10.1158/0008-5472.can-08-2155
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone Down-regulates Chemokine Receptor CXCR4 Expression Leading to Inhibition of CXCL12-Induced Invasion of Breast and Pancreatic Tumor Cells

Abstract: CXC chemokine receptor 4 (CXCR4), initially linked with leukocyte trafficking, is now known to be expressed in various tumors including breast, ovary, prostate, gastrointestinal, head and neck, bladder, brain, and melanoma. This receptor mediates homing of tumor cells to specific organs that express the ligand CXCL12 for this receptor. Thus, agents that can down-regulate CXCR4 expression have potential against cancer metastasis. In this study, we report the identification of zerumbone, a component of subtropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 45 publications
2
89
0
Order By: Relevance
“…Additionally, CXCR7 expression was associated with the proliferation rate of gastric MALT lymphomas and extranodal diffuse large B-cell lymphoma in our study. CXCL12-the ligand of CXCR4 and CXCR7 20-22 -has been linked to multiple key processes in tumor cells, including proliferation, survival, migration, invasion and metastasis in more than 20 different types of cancer, [42][43][44][45][46][47][48][49] providing evidence for the importance of this chemokine signaling pathway in cancer. CXCR7 expression was described in malignant cell types, in fetal liver cells and on tumor-associated blood vessels but not in normal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CXCR7 expression was associated with the proliferation rate of gastric MALT lymphomas and extranodal diffuse large B-cell lymphoma in our study. CXCL12-the ligand of CXCR4 and CXCR7 20-22 -has been linked to multiple key processes in tumor cells, including proliferation, survival, migration, invasion and metastasis in more than 20 different types of cancer, [42][43][44][45][46][47][48][49] providing evidence for the importance of this chemokine signaling pathway in cancer. CXCR7 expression was described in malignant cell types, in fetal liver cells and on tumor-associated blood vessels but not in normal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these previous reports, our immunohistochemical results indicate CXCR4 expression in pancreatic tumor tissues. CXCR4 expression increases metastatic potential of pancreatic cancer cells in vivo, resulting in liver and lung metastasis in a mouse model (Saur et al, 2005), whereas CXCR4-specific shRNA or zerumbone, a compound that negatively regulates CXCR4 expression, inhibits pancreatic cancer cell invasion (Sung et al, 2008;Wang et al, 2008). Furthermore, it is suggested that a subpopulation of migrating CD133 þ CXCR4 þ pancreatic cancer stem cells is essential for tumor metastasis (Hermann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal and co-workers also reported the potential suppressive effects of zerumbone on the chemokine receptor CXCR4 [51], which is found to be overexpressed in several tumors [52]. Zerumbone suppressed both human epidermal growth factor receptor 2 (HER2)-induced CXCR4 expression in MCF7 breast cancer cell lines and constitutive CXCR4 expression in a variety of cancer cell lines such as leukemia (KBM-5), myeloma (U266), head and neck squamous cell carcinomas (SCC4), kidney carcinoma (A293), lung adenocarcinoma (H1299) and pancreatic carcinoma (PANC-1, PANC-28 and MIA PaCa-2).…”
Section: Cem-ss Cells (T-acute Lymphoblastic Leukemia)mentioning
confidence: 98%